Applications of Digital Photogrammetric Systems for Dimensional Measurement and 3D Modelling - Setan, Halim; Ibrahim, M. S.; Ma'arof, Ismail (2004)
One of the important current development in digital close range photogrammetric systems is the full automation of the measuring process. The systems range available from low to high accuracy. This study focuses on the applications of low accuracy (using normal digital camera) and high accuracy (using V-STARS system) digital close range photogrammetric systems for dimensional measurement and 3D modeling of several objects. The accuracy were checked with other systems, i.e. AXYZ and CMM. The results obtained show the practicality of both systems, with accuracy ranging from several micron (for high accuracy system) to several mm (for low accuracy system).